PEMAHAMAN STRUKTUR DAN MAKNA KOSAKATA KANJI JUKUGO PADA MAHASISWA TINGKAT III PENDIDIKAN BAHASA JEPANG TAHUN AJARAN 2017/2018 - Resa Mustapa Akbar; Arza Aibonotika; Hana Nimashita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This research is discuss the understanding of jukugo kanji vocabulary’s structure and meaning on III grade of students of Japanese language education of Riau University 2017/ 2018. The purpose of this research is to measure students ability and comprehension on jukugo kanji. Then, to explain the difficulty of the jukugo kanji comprehension. This research used quantitative descriptive method by using survey as the research design. The data were collected by using test and interview the respondents. This research was done as a quantitative research in the field of education. All data were analyzed using statistic method and the result explained by descriptive method to describe the result. Based on the results of the test, it can be seen that the overall level of students' understanding of the jukugo kanji comprehension is at level B+ or Good, at the interval 75-79,99with an average of 76.24. The test results show that the highest score is 96 and the lowest score is 32. The test result also supported by the interview result, respondents are always have a problem in comprehension of jukugo kanji.cause respondents are difficult to remind of kanji have been studied. Moreover, based on the interview result respondents are the lack of jukugo kanjivocabulary mastery cause of training less.Keywords : understanding, structure, meaning,jukugo kanji